1979
DOI: 10.1111/j.1365-2125.1979.tb04705.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and clinical importance of narcotic antagonists and mixed antagonists‐use in cardiology.

Abstract: 1 The treatment of pain of cardiac origin requires a knowledge of the haemodynamic action of the analgesic agents used. 2 The haemodynamic effects of morphine, diamorphine, pavaveretum, pethidine and pentazocine are reviewed. 3 Clinical experience with the new antagonist analgesic buprenorphine is reported. 4 These studies indicate that buprenorphine may be the agent of choice for the relief of severe pain in patients with unstable circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It probably relates primarily to the concentration of the drug achieved at mast cell membrane (1 7). Coltart & Malcolm (19) reported that "buprenorphine does not seem to cause histamine release", but this statement was not supported by clinical or experimental observations. Therefore, we can assume that buprenorphine, which is 30-40 times as potent an analgesic as morphine (18), may not cause histamine release since very low amounts (0.2-0.4 mg) are required to achieve clinically useful effects.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It probably relates primarily to the concentration of the drug achieved at mast cell membrane (1 7). Coltart & Malcolm (19) reported that "buprenorphine does not seem to cause histamine release", but this statement was not supported by clinical or experimental observations. Therefore, we can assume that buprenorphine, which is 30-40 times as potent an analgesic as morphine (18), may not cause histamine release since very low amounts (0.2-0.4 mg) are required to achieve clinically useful effects.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, we can assume that buprenorphine, which is 30-40 times as potent an analgesic as morphine (18), may not cause histamine release since very low amounts (0.2-0.4 mg) are required to achieve clinically useful effects. Coltart & Malcolm (19) reported that "buprenorphine does not seem to cause histamine release", but this statement was not supported by clinical or experimental observations. Buprenorphine, which is a derivative of thebain, bears a close structural resemblance to morphine (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…14 Because of its apparent lack of cardiovascular effects, buprenorphine has been suggested as a preferred treatment for severe pain control in patients with unstable hemodynamic parameters. 15 Buprenorphine inhibits the human ether-a-gogo-related gene (HERG) I Kr in vitro. 4 However, to our knowledge, no cases of cardiac arrhythmia related to this compound have been documented.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, attention must be paid to dosage and speed of administration, particularly where a preexisting pathological condition may affect cardiovascular competence, that is, in acute or chronic shock or in cardiac insufficiency. The cardiovascular effects of agonist and antagonist analgesics (including pentazocine and buprenorphine) are reviewed elsewhere in these Proceedings (Coltart & Malcolm, 1979).…”
Section: Cardiovascular Effectsmentioning
confidence: 99%